EVALUASI PERENCANAAN BREAKWATER TERHADAP GELOMBANG DI PELABUHAN PERIKANAN PANTAI PASONGSONGAN, JAWA TIMUR - Irza Nensita Mayanda; Cholilul Chayati; Ach. Desmantri Rahmanto (Fakultas Sains dan Teknologi Universitas Ngurah Rai, 2023)
Pasongsongan Beach Fishing Harbor is included in class C fishing ports. The main facility at Pasongsongan Beach Fisheries Harbor is a Breakwater which was built with a length of 50 m and a width of 18 m, but it cannot protect the anchoring pond from sedimentation due to tidal currents carrying sedimentary material. enter the anchor pool so that the water depth in the anchor pool experiences shallowing due to sedimentation. Therefore, it is necessary to evaluate the breakwater planning at Pasongsongan Beach Fishing Harbor with the aim of reducing sedimentation in the harbor pond. The research method used is a quantitative descriptive method. By analyzing winds, waves and tides for 4 years. Based on the evaluation results obtained, a breakwater length of 60 m is planned with a breakwater height at the head end of the building of 4.176 m and a width of 16.55 m. Meanwhile, the height of the breakwater on the arm of the building is 4.176 m and the width is 16.07 m. The type of breakwater planned is a sloping side type made from tetrapod material and crushed stone with a building slope of 1:2. The specifications for the head end use tetrapod stone, the first layer weighing 0.434 tons and the second layer weighing 0.0434 tons, while the core layer uses rough natural stone weighing 0.00408 tons. For the arms of the building, tetrapod stone is used, the first layer weighs 0.279 tonnes and the second layer weighs 0.0279 tonnes, while the core layer uses rough natural stone weighing 0.00326 tonnes.